MINIMALLY INVASIVE APPROACH FOR RIGHT-SIDED COLON CANCER, COMPLICATED BY LARGE-BOWEL OBSTRUCTION - A. I. Chernookov; A. G. Mylnikov; A. N. Garunov; L. A. Marinova; M. M. Karapetyan; M. V. Kosachenko; S. A. Zavodchikov; A. P. Moiseyev (Неотложная медицинская помощь, 2017)
The case demonstrates an opportunity of safe and successful colonic stenting to treat bowel obstruction with following laparoscopic radical intervention for right-sided colon cancer localization. The colonic stent as a “bridge to the surgery” improves immediate results and surviving rate in elderly patients with complicated right-sided colon cancer and severe concomitant disease.